Determinan Ekonomi Terhadap Keikutsertaan Program Jaminan Kesehatan Nasional (JKN) Di Kota Madiun Tahun 2023 - Anindita Hasniati Rahmah; Rury Narulita Sari; Yuli Kusumawati; Widya Kaharani Putri; Nurul Fatimah (Pusat Riset dan Inovasi Nasional, 2023)
National Health Insurance (JKN) is a priority for low- and middle-income countries as a way to increase access to health services and reduce the financial burden on health care. The special objective is to analyze the relationship between income and participation in the National Health Insurance (JKN). The 30 respondents, 19 (63.3) respondents were female and 11 (26.7) were male. And aged > 45 years old a total of 15 (50.0) and < 45 years old (50.0). And almost all 23 respondents (69.7) earned < 2,190,206 in each month and as many as 7 respondents with an income of > 2,190,206 in each month. There is a significant positive relationship between the level of opinion and participation in the National Health Insurance program, where the higher the income, the more people participate in the National Health Insurance program. Comprehensive and comparable estimates of health spending across countries are critical to achieving national and international health goals. If there is more health care, the amount of premium that will be issued will also be a lot. Premium increases in the health insurance sector are an uphill task for policymakers to form balanced policies that can provide affordable health care while maintaining survival